Studi Literatur : Peran Audit Kinerja dalam Meningkatkan Akuntabilitas dan Efisiensi Sektor Publik di Indonesia - Yulisfan Yulisfan; Yola Dwi Afila; Abdul Habib Sitompul; Dedi Agus Pratikno; Rina Ananda; Adilla Fiqria (BADAN PENERBIT STIEPARI PRESS, 2025)
Performance audit is a vital tool in the public sector oversight system aimed at assessing the efficiency, effectiveness, and economy of public financial management. This study aims to systematically examine the role of performance audit in enhancing accountability and efficiency in Indonesia's public sector through a literature review approach. The data sources include scholarly journals, audit reports from the Audit Board of Indonesia, and other theoretical references published between 2017 and 2024. The results indicate that performance audits significantly contribute to improving transparency, accountability, and budget management. However, the implementation of performance audits still faces challenges such as limited human resources, weak follow-up on audit recommendations, and lack of integration between audit results and planning processes. Therefore, strengthening institutional capacity and improving auditor competency are essential strategies to optimize the role of performance audits in Indonesia’s public sector